2001
DOI: 10.1074/jbc.m007065200
|View full text |Cite
|
Sign up to set email alerts
|

Outside-in Signaling Pathway Linked to CD146 Engagement in Human Endothelial Cells

Abstract: CD146 (S-Endo 1 Ag or MUC18) is a transmembraneCas tyrosine phosphorylation. Moreover, a complex association was observed between Pyk2, p130Cas , and paxillin. These results indicate that CD146 is coupled to a FYN-dependent pathway that triggers Ca 2؉ flux via phospholipase C-␥ activation leading subsequently to the tyrosine phosphorylation of downstream targets such as Pyk2, p130Cas , FAK, and paxillin. In addition to its role in cell-cell adhesion, CD146 is a signaling molecule involved in the dynamics of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
117
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 60 publications
(50 reference statements)
2
117
0
3
Order By: Relevance
“…The intracellular domain promotes the recruitment of the Src family kinase FYN as well as tyrosine phosphorylation of several intracellular proteins, including FAK (and paxillin), that are present in focal adhesion plaques. 37,50,51 We observed increased FAK and FYN immunostaining in breast carcinomas of poor outcome compared with tumors from patients with longer survival. This is probably a result of increased cellular signals from cMet and CD146, which both act through FYN signaling pathways upon angiogenesis and rearrangement of the actin skeleton.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The intracellular domain promotes the recruitment of the Src family kinase FYN as well as tyrosine phosphorylation of several intracellular proteins, including FAK (and paxillin), that are present in focal adhesion plaques. 37,50,51 We observed increased FAK and FYN immunostaining in breast carcinomas of poor outcome compared with tumors from patients with longer survival. This is probably a result of increased cellular signals from cMet and CD146, which both act through FYN signaling pathways upon angiogenesis and rearrangement of the actin skeleton.…”
Section: Discussionmentioning
confidence: 60%
“…This is probably a result of increased cellular signals from cMet and CD146, which both act through FYN signaling pathways upon angiogenesis and rearrangement of the actin skeleton. [49][50][51] Experimental studies have shown that anti-CD146 monoclonal antibodies inhibit proliferation and migration of endothelial cells and angiogenesis, reflected by a reduction in blood vessel density associated with tumor growth inhibition. 51 This treatment exhibited no cytotoxic effects in animals, and its efficacy increased when the anti-CD146 monoclonal antibody AA98 was combined with other anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…MCAM can mediate homophilic cell-cell adhesion, as well as heterophilic adhesions, through interaction with an unknown ligand. MCAM has been shown to activate intracellular signaling pathways and to regulate cell growth (32,33). MCAM inhibition attenuated tumor growth and metastasis by inhibition of interaction between melanoma cells and endothelial cells (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…On cultured endothelial cells, CD146 is mainly located at the intercellular junctions and is involved in inter-endothelial cell adhesion and paracellular permeability [11,12]. CD146 cross-linking in HUVEC induces a tyrosine phosphorylation of the non-receptor tyrosine kinase p59 fyn , of focal adhesion kinase and of paxillin, suggesting a role of CD146 in the reorganization of the cytoskeleton [13,14]. Several lines of evidence from the literature point out a role of CD146 in vascular development.…”
mentioning
confidence: 99%